(untitled) (Third Sector Social Economic Review, 2026)
The telecommunications industry is undergoing a paradigm shift, evolving from traditional connectivity providers into digital ecosystem players, with Embedded Finance (EmFi) emerging as a critical growth engine. There is a notable lack of empirical research on embedded finance on micro-level performance metrics, particularly in non-bank sectors. This study empirically investigates the long-run impact of embedded finance revenue streams on Turkcell’s corporate market value, a leading telecommunications operator in Turkey. Drawing on multiple theoretical frameworks, the research posits that embedded finance fosters firm value by reducing transaction friction and creating lock-in effects. Using quarterly financial data from 2016Q4 to 2025Q3, the study employs the Autoregressive Distributed Lag (ARDL) bounds testing approach to analyze the cointegration dynamics between the company’s embedded finance integration and its market capitalization. The empirical results confirm the existence of a cointegration relationship, demonstrating that embedded finance revenues are a positive and significant determinant of the firm’s long-run market value. These findings imply that investing in digital financial services is not merely a diversification strategy but a fundamental driver of shareholder value. The study contributes to the limited literature on non-bank financial providers by offering empirical evidence from an emerging market context.